2004
DOI: 10.1007/s11243-004-4993-8
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(II) complexes containing triphenylphosphine/triphenylarsine and bidentate Schiff bases derived from 2-hydroxy-1-naphthaldehyde and primary amines

Abstract: The synthesis and characterisation of some new hexa-coordinated Schiff base complexes of the type [RuCl(CO)(EPh 3 )(B)(L)] (E ¼ P or As; B ¼ PPh 3 or AsPh 3 or py or pip; L ¼ anion of the Schiff bases derived from 2-hydroxy-1-naphthaldehyde and aniline, 4-chloroaniline or 2-methylaniline) are reported. I.r., electronic, 1 H-n.m.r, 31 P-n.m.r. spectra, catalytic activity and antibacterial activity of the complexes are discussed. An octahedral structure has been tentatively proposed for all the complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…All of the complexes have a medium to strong band in the region 1944–1932 cm –1 , which is attributed to the terminally coordinated carbonyl group (CO), appearing at a somewhat higher frequency than the precursor complexes . In the spectra of the complexes, the distinctive absorption bands due to PPh 3 /AsPh 3 were also observed in the predicted regions. , …”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…All of the complexes have a medium to strong band in the region 1944–1932 cm –1 , which is attributed to the terminally coordinated carbonyl group (CO), appearing at a somewhat higher frequency than the precursor complexes . In the spectra of the complexes, the distinctive absorption bands due to PPh 3 /AsPh 3 were also observed in the predicted regions. , …”
Section: Resultsmentioning
confidence: 86%
“… 32 In the spectra of the complexes, the distinctive absorption bands due to PPh 3 /AsPh 3 were also observed in the predicted regions. 33 , 34 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there has been a growing interest in the last few years in these ligands and their metal complexes due to the broad spectrum of biological properties they possess, such as antifungal, antibacterial, anti-inflammatory, antiviral, anticonvulsant, antidepressant, anticancer along with good anti-HIV activity and structural similarities with natural biological substances [8][9][10][11][12]. The biological activity is mainly due to the presence of the imine (-N=CH-) and the thiazo (-N-C=S) groups near one another [13,14]. Biological properties of thiosemicarbazones have been studied since 1956 when Brockman et al reported the antitumour activities of thiosemicarbazones derived from 2-formylpyridine and recently it has been developed as an antitumour drug and has received clinical phase II on several cancer types [15,16].…”
Section: Introductionmentioning
confidence: 99%